Assessment of leucoreduction of sickle cell trait blood: quality of the filtered product - Amar, Karim Ould; Bourdonné, Olivier; Bruneau, Sylvie; Sellami, Fatiha; Richard, Pascale (Blood transfusion = Trasfusione del sangue, 2014)
With the implementation of universal leucoreduction of blood components in several industrialised countries, the problems associated with leucocyte filtration of sickle cell trait blood have been reconsidered. In this study, we assessed the use of high performance filters for leucoreduction of packed red blood cells donated from subjects with sickle cell trait and evaluated the incidence and recurrence of altered red blood cell filterability. Twenty-one volunteer donors with HbAS were compared to 21 donors with HbAA selected at random. The main parameters analysed were residual white blood cell count and post-filtration haemolysis. Filtration times, flow, volume and haemoglobin loss of the packed red blood cells were also determined. In all, 33% of HbAS red blood cell units with slow flow and prolonged filtration time had high residual white blood cell counts. In 7.7% of cases, despite flow through the filter, the units were not leucoreduced properly. Haemoglobin and volume loss were significantly greater in the slow filtration group. Significant post-filtration haemolysis was present in half of the units with high residual white blood cell counts. Despite the development of new technology for filtration, the problem of filterability of blood from donors with sickle cell trait is not yet resolved. Altered filterability of blood from sickle cell trait donors cannot be predicted from the donors' characteristics and recurrence of the problem is not observed between donations. Screening blood donors for sickle cell trait to ensure the safety and quality of blood products for transfusion does, therefore, remain a relevant issue.